Europejska Polityka Sąsiedztwa : konstrukcja i charakter prawny - Kalicka-Mikołajczyk, Adriana (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
This publication is devoted to the legal structure and the legal nature of the European Neighbourhood Policy (ENP). The analysis of those issues is the aim of the deliberations contained in the present work, and thus delineates their extent. This is going to allow, as a consequence, for the description of further defining traits of the entire mechanism of the ENP’s functioning, with said mechanism understood here as a collection of instruments for the operation of this policy. There is a hypothesis adopted in this work that the ENP was accorded a special legal structure, on the basis of the instruments concluded and adopted within the framework of this policy, and said structure directly affects its legal nature. The legal basis of the ENP is Article 8 TEU. According to paragraph 1 thereunder, “the Union shall develop a special relationship with neighbouring countries, aiming to establish an area of prosperity and good neighbourliness, founded on the values of the Union and characterised by close and peaceful relations based on cooperation”. The aim of such cooperation is to develop a “special relationship” between the EU and neighbouring countries, that are to be “close, peaceful and based on cooperation”, causing “an area of prosperity of good neighbourliness to be established”. However, and this must be greatly stressed, there is no answer under the provisions of this Article to the question of which instruments are to be used to achieve that aim. The general interpretative guidance is contained within the provisions of paragraph 2, pursuant to which a competence was conferred on the Union, in that it may conclude “specific agreements” with the neighbouring countries, on such a condition that the EU “may” and not “must” conclude an international agreement of that type with a neighbouring country. This means that the EU was allowed a right to choose the form of a given instrument(s), with which the achievement of the aim of cooperation with neighbouring countries provided for under paragraph 1 would occur. Therefore, the issue of an answer to the question of instrument(s) with the help of which is this policy implemented is left unresolved. And, among other things, this is the question to which this monograph is to give an answer.
Keywords: European Neighbourhood Policy; European Union; art. 8 TEU; EU values; coherence; Eastern Partnership; association agreement; action plan